2019
DOI: 10.1111/ijd.14338
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone wallpapers for dermoscopy training in medical students and residents

Abstract: Background Several dermoscopy training programs have found the accuracy of dermoscopy examination depends on adequate training of practitioners. Smartphones are readily available and time-efficient tools for dermoscopy training.Aim To evaluate the learning efficacy of utilizing dermoscopy smartphone wallpapers to train medical students, PGY (postgraduate year)-1 trainees, and junior dermatological residents without prior dermoscopy training. Methods We designed smartphone wallpapers with dermoscopy pictures an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Finally, it is essential to mention the economic factor, previously related in a similar study (19), that causes less use of smartphones for educational tasks, which could mean a barrier for students of academic groups who probably prefer to use texts in physical or digital through the laptop, an ICT of diversified use in university. Despite this, this negative relationship should be corroborated in future similar studies, because there is also literature that affirms the potential benefit of Smartphone use in the educational area, particularly in undergraduate (20)(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 95%
“…Finally, it is essential to mention the economic factor, previously related in a similar study (19), that causes less use of smartphones for educational tasks, which could mean a barrier for students of academic groups who probably prefer to use texts in physical or digital through the laptop, an ICT of diversified use in university. Despite this, this negative relationship should be corroborated in future similar studies, because there is also literature that affirms the potential benefit of Smartphone use in the educational area, particularly in undergraduate (20)(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 95%
“…The participants underwent pre- and posttests without any formal teaching in between, resulting in an overall improvement in diagnostic accuracy. 18 …”
Section: Discussionmentioning
confidence: 99%
“…The participants underwent pre-and posttests without any formal teaching in between, resulting in an overall improvement in diagnostic accuracy. 18 Although there is robust evidence in the literature that dermoscopy can improve diagnostic accuracy among plastic surgeons and general practitioners, there is a scarcity of data on the potential benefits of specific training for plastic surgery residents. Pescarini et al addressed this gap by retrospectively evaluating the performance of three plastic surgery registrars with similar skin cancer experiences and training in detecting malignant skin lesions.…”
Section: Discussionmentioning
confidence: 99%
“…A review of published literature reported the uses of mobile computing technologies (i.e. PDAs, tablet computers and smartphones) in medical settings for clinical, educational, and research activities (Akkerman and Filius, 2011; Burdette, Herchline and Oehler, 2008; Ozdalga, Ozdalga and Ahuja 2012; Sclafani, Tirrell and Franko 2013; Stergiannis, Intas, Toulia, et al, 2017; Tahamtan, Pajouhanfar, Sedghi, et al, 2017; Wang, Liu, Chuang, et al, 2019). These technologies are being integrated into clinical practice by physicians, residents and medical health providers with different specialties (Blake, 2008; Dala-Ali, Lloyd and Al-Abed, 2011; Tempelhof, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%